2010
DOI: 10.1089/jmf.2010.1165
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Carotenoids and Chlorophylls from Gynostemma pentaphyllum (Thunb.) Makino and Their Antiproliferation Effect on Hepatoma Cell

Abstract: A preparative column chromatographic method for isolation of carotenoids and chlorophylls from Gynostemma pentaphyllum, a traditional Chinese herb, was developed to evaluate their antiproliferative effects on the hepatoma cell Hep3B. An open column containing 70 g of magnesium oxide-diatomaceous earth (1:2.5, wt/wt) was used to elute carotenoid with 2% ethanol in ethyl acetate and chlorophyll with 50% ethanol in acetone. After high-performance liquid chromatography-mass spectrometry analysis, the carotenoid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Some herbs are demonstrated to be potent to arrest cell cycle. Among tonic herbs, extracts of JiaoGuLan (Gynostemma pentaphyllum) can inhibit proliferation and arrest cell cycle at G0/G1 phase in Hep3B cells [134,135] . Triterpeneenriched extracts from LingZhi (Ganoderma lucidum) could suppress protein kinase C, activate JNK and p38 mitogenactivated protein kinases (MAPK) to prolong G2 cell cycle phase and inhibit cell growth in Huh7 cells [136] .…”
Section: Arresting Cell Cyclementioning
confidence: 99%
“…Some herbs are demonstrated to be potent to arrest cell cycle. Among tonic herbs, extracts of JiaoGuLan (Gynostemma pentaphyllum) can inhibit proliferation and arrest cell cycle at G0/G1 phase in Hep3B cells [134,135] . Triterpeneenriched extracts from LingZhi (Ganoderma lucidum) could suppress protein kinase C, activate JNK and p38 mitogenactivated protein kinases (MAPK) to prolong G2 cell cycle phase and inhibit cell growth in Huh7 cells [136] .…”
Section: Arresting Cell Cyclementioning
confidence: 99%
“…Gynostemma pentaphyllum ( G. pentaphyllum ), also known as “Jiaogulan”, is commonly referred to the poor’s ginseng and is widely used as a folk medicine and herbal tea in Asian countries, including Taiwan, China, Japan, and Korea. Several vital biological activities including anti-cancer [3,4,5,6,7,8,9] anti-inflammation [10,11,12], anti-oxidation [13,14], anti-hyperglycemic [15,16,17] and anti-atherosclerosis effects [15,18,19,20] have been associated with intake of G. pentaphyllum . The major bioactive components of G. pentaphyllum in order of abundance include saponins, flavonoids, chlorophylls, and carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms are a potentially great source of natural compounds that could be used as functional ingredients (Plaza, Herrero, Cifuentes, & Iban~ez, 2009). Chlorophylls and carotenoids are present abundantly in green plants and possess important biological activities including antioxidant (Tsai, Wu, & Chen, 2010), antitumour (Tsai et al, 2010) and anti-invasion (Kozuki, Miura, & Yagasaki, 2000). According to Wu, Wu, and Shi (2007) Chlorella contained 2-4 mg/g dry cell weight of lutein.…”
Section: Discussionmentioning
confidence: 99%
“…Cha, Koo, and Lee (2008) reported that the bioactive carotenoid, xanthophylls of Chlorella ellipsoidea exerted strong antiproliferative effects on human colon cancer cells. Tsai et al (2010) reported that carotenoids and chlorophylls isolated from Gynostemma pentaphyllum had antiproliferative effect on hepatoma cells. In this study, GPE contain lutein, chlorophyll a, and chlorophyll b and they may have contributed, in a substantial part at least, to the antitumour and anti-invasion activities of GPE.…”
Section: Discussionmentioning
confidence: 99%